Epidemiology of Kawasaki disease in Australia using two nationally complete datasets. (30th October 2021) - Lucas, Ryan; Dennington, Peta; Wood, Erica; Murray, Kevin J; Cheng, Allen; Burgner, David; Singh‐Grewal, Davinder
Abstract : Aim: The incidence of Kawasaki disease (KD) is reported to be increasing in some populations. We sought to describe long‐term trends in the incidence and epidemiology of KD in Australia over 25 years. Methods: Two nationally complete administrative datasets relevant to KD in Australia were analysed and compared. The Australian Red Cross Lifeblood Supply Tracking Analysis Reporting System (STARS) recorded all doses of immunoglobulin (IVIG) approved in Australia between January 2007 and June 2016. The Australian Institute of Health and Welfare National Hospital Morbidity Database (NHMD) records all episodes of care in hospitals across Australia. Data relevant to KD were extracted an analysed, with comparisons made for the period of data overlap. Results: During the period of data overlap (2007–2015) the IVIG treatment rate in the 0‐ to 4‐year age group (calculated from STARS) was 14.31 per 100 000 person‐years (95% confidence interval 13.67–14.97). The hospitalisation rate in the same age group (calculated from the NHMD) was 14.99 per 100 000 person‐years (95% confidence interval 14.33–15.66). Hospitalisation rates rose at an average rate of 3.54% annually over the 25 years to 2017 in the 0‐ to 4‐year age group, almost exclusively in the 1‐ to 4‐year age group. Conclusions: There is evidence of increasing KD diagnosis in Australia. Similar trends have also been reported in Asia but not in North America or Europe. Increasing diagnosis may reflect a true increase in disease incidence, increasing recognition or overdiagnosis. Further research is needed to determine the cause for these trends.